The regionalisation of innovation policy in Germany: theoretical foundations and recent experience - Knut Koschatzky (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2000)
In recent years, not only has the network paradigm become the starting-point for policy measures aiming at a better exploitation of innovation potentials, but also the region, i.e. sub-national spatial entities, has been made an important platform for innovation policy implementation by national governments. Specifically, the cluster concept and other theoretical approaches of the new economic geography contributed to the popularisation of regional development concepts. A substantial feature of this focus on the region is that measures, which have so far had a national orientation (and for those the question about the distribution of innovative potentials in space was not or was only implicitly raised), have to be adapted to the specific structures and potential of individual regions. However, not every region in a country can develop into a high-tech island equipped with leading-edge technology, industry and research. For many regions and their economic actors, the only development option is to carry out supplementary functions for other regions, clusters and economic activities or to focus on the exploitation of endogenous potential and strengths. ...
urn:nbn:de:0011-n-36441
Keywords: 330; Innovationspolitik; Forschungs- und Technologiepolitik; Regionalpolitik; Dezentralisierung; Unternehmensgründung; Theorie; Deutschland; Wirtschaftsförderung